A Customized Mobile Application in Colonoscopy Preparation: A Randomized Controlled Trial. Issue 1 (January 2017) - Sharara, Ala I; Chalhoub, Jean M; Beydoun, Maya; Shayto, Rani H; Chehab, Hamed; Harb, Ali H; Mourad, Fadi H; Sarkis, Fayez S
Abstract : OBJECTIVES: : Adherence with diet and prescribed purgative is essential for proper cleansing with low‐volume bowel preparations. The aim of this work was to assess the effect of a customized mobile application (App) on adherence and quality of bowel preparation. METHODS: : One hundred and sixty (160) eligible patients scheduled for elective colonoscopy were randomly assigned to paper (control) or App‐based instructions. The preparation consisted of low‐fiber diet for 2 days, clear fluids for one day and split‐dose sodium picosulfate/magnesium citrate (SPS). Before colonoscopy, information was collected regarding adherence with, and utility of the provided instructions. The colonoscopists, blinded to assignment, graded bowel preparation using the Aronchick, Ottawa, and Chicago preparation scales. The primary endpoint was adherence with instructions. Quality of preparation was a secondary endpoint. RESULTS: : No difference in overall adherence or bowel cleanliness was observed between the study arms. Adherence was reported in 82.4% of App vs. 73.4% of controls ( P =0.40). An adequate bowel preparation on the Aronchick scale was noted in 77.2 vs. 82.5%, respectively ( P =0.68). Mean scores on the Ottawa and Chicago scales were also similar. Gender, age, time of colonoscopy, and BMI did not influence preparation or adherence. Compliance with the clear fluid diet component was noted in 94% of patients with BMI<30 vs. 77% with BMI≥30 ( P <0.01). SPS was well tolerated by 81.9% of patients. The App was user‐friendly and received higher overall rating in this respect than paper instructions ( P <0.01). CONCLUSIONS: : SPS is well tolerated and effective for bowel cleansing regardless of instruction method. Customized smartphone applications are effective, well‐accepted and could replace standard paper instructions for bowel preparation. ClinicalTrials.gov: NCT02410720